1998
DOI: 10.1177/0022427898035002005
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk of Crime in the Czech Republic

Abstract: The authors examine models of the perceived increased risk of crime in the Czech Republic derived from both American criminology and research on the perception of risk. The sample is 740 households in the 1994 Czech Republic, with 577 husband and wife respondents, 146 single female household heads, and 17 single male household heads. Measures include criminal victimization, personal characteristics associated with exposure and vulnerability to crime, trust in government, economic stress, as well as perceived i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…These studies all contrast these measures of cognitive risk perceptions of safety (risk) with fear of crime measures of worry that examine the emotional aspect of fear. Hraba et al (1998) used the perception of the increase of crime as their measure of perceived risk and Mesch (2000) used the perception of neighbourhood criminality and the number of criminals in the neighbourhood as their risk perception measure. The majority of the research that explores perceived risk of criminal victimization has been carried out in the USA with only a few exceptions: Brazil (Villarreal and Silva, 2006), Israel (Mesch, 2000) and the Czech Republic (Hraba et al, 1998).…”
Section: Aims and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies all contrast these measures of cognitive risk perceptions of safety (risk) with fear of crime measures of worry that examine the emotional aspect of fear. Hraba et al (1998) used the perception of the increase of crime as their measure of perceived risk and Mesch (2000) used the perception of neighbourhood criminality and the number of criminals in the neighbourhood as their risk perception measure. The majority of the research that explores perceived risk of criminal victimization has been carried out in the USA with only a few exceptions: Brazil (Villarreal and Silva, 2006), Israel (Mesch, 2000) and the Czech Republic (Hraba et al, 1998).…”
Section: Aims and Methodsmentioning
confidence: 99%
“…This difference in measure may explain the different directions of the effects found for this variable, as they may be influenced by different factors. Hraba et al (1998) highlighted the context in which their study took place À a turbulent time with extreme economic instability after the collapse of communism and the split of Czechoslovakia into the Czech Republic and Slovakia, with huge increases in the level of crime. Yet they provide no objective measure of the crime rate and therefore their measure of perceived increase in the level of crime has no data to which it can be compared, and so it is not clear whether the perception of a high increase in crime is an inflated perception or an accurate observation of the situation.…”
Section: Hicks and Brownmentioning
confidence: 99%
“…For example, criminologists have found a positive (LaGrange and Ferraro, 1989), negative (Rountree and Land, 1996), or nonexistent (Hraba et al, 1998;Mesch, 2000) relationship between perceived risk of criminal victimization and age. Additional studies on public risk perceptions of natural disasters, automobile accidents, cancer and other risks also show that the relationship between age and risk perception is mixed.…”
Section: Agementioning
confidence: 99%
“…Two studies using data for the United States (Skogan and Maxfield 1981;Toseland 1982) as well as a study using Australian data (Borooah and Carcach 1997) found that a higher income was associated with a reduced fear of crime. On the other hand, Hraba et al (1998) found that wealth was positively related to perceived risk of crime in the Czech Republic, arguing that this reflected the fact that "the wealthy may feel vulnerable to crime, particularly property crime" Hraba et al (1998, p.239). We will explore the nature of the income/public security perception relationship to see which effect, if either, dominates in urban China.…”
Section: Incomementioning
confidence: 99%